Thermal degradation behaviours, VOCs emission characteristics, and environmental impacts during pyrolysis recycling of waste enamelled wires - Fan, Chunlong (Environmental technology, 2024)
Waste enamelled wires represent a significant secondary copper resource, often processed through pyrolysis for material recovery. However, the release of VOCs during pyrolysis poses environmental challenges. This study investigated the thermal degradation behaviour and VOCs emission characteristics of waste enamelled wires during pyrolysis. Kinetic analysis revealed that the pyrolysis process can be divided into three stages, with the activation energy increasing from 190.56 kJ/mol in the initial stage to 552.33 kJ/mol in the final stage. The optimal pyrolysis temperature and holding time were identified as 800°C and 30 min, respectively. The maximum VOCs emission concentration reached 28224.8 μg/m³ in the temperature range of 550-650°C, with ethers being the dominant contributors. The study also calculated the OFP, with the highest value of 66866.85 μg/m³ observed during the 550-650°C temperature range. These findings provide important guidance for controlling VOCs emissions during pyrolysis to minimize environmental impacts